Vanadia/silica xerogels and nanocomposites - Stiegman, A. E; Eckert, Hellmut; Plett, Gary; Kim, Soon Sam; Anderson, Mark; Yavrouian, Andre (Chemistry of materials, 1993)
The application of the sol-gel process to the synthesis of dense oxide glasses and ceramics has been the subject of escalating interest because of the low temperatures and compositional flexibility inherent in this purely chemical approach. More recently it has been realized that undensified silica [open quotes]xerogel[close quotes] materials possess unique properties precisely because of their porous nature. The authors report the synthesis of a new transparent metal containing silica gel by the co-condensation of low concentrations of oxovanadium triisopropoxide with tetraethylorthosilicate (TEOS) via the sol-gel process.